Exploring Students’ Understanding of English Tenses Through Writing - Annisa Zahra Hasibuan; Dhea Prasisca; Karmida; Aisyah Putri Sitorus (Indonesian Journal of ELT and Applied Linguistics, 2022)
English grammar and Indonesian grammar are different in some ways. One of the differences can be seen in constructing sentences based on referring time . The difference of grammatical structure between English and Indonesian which will be learnt especially is tenses for verbal sentences because in verbal sentences the rewill be shown the transformation of verb which does not occur in Indonesian structure. Therefore the researchers using Report Text material in spesifically about students’ experience, then There are four students which will be observed by the researchers. the method- research using is the descriptive method or what is usually called the qualitative method.And qualitative data will submitted by observing a hand-writting from the students.